2008
DOI: 10.1038/sj.bjc.6604358
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-dependent signalling pathway are involved in the early process of radiation-induced bystander effects

Abstract: Bystander effects induced by cytoplasmic irradiation have been reported recently. However, the mechanism(s) underlying, such as the functional role of mitochondria, is not clear. In the present study, we used either mtDNA-depleted (r 0 ) A L or normal (r þ ) A L cells as irradiated donor cells and normal human skin fibroblasts as receptor cells in a series of medium transfer experiments to investigate the mitochondria-related signal process. Our results indicated that mtDNA-depleted cells or normal A L cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 30 publications
7
51
0
Order By: Relevance
“…3) clearly shows that irradiated rho + yeast cells induced BE is much stronger than the rho 0 cells. These results confirm the view that strength of bystander effect depends on existence of mitochondrial DNA and normally functioning mitochondria [4].…”
Section: Manifestation Of the Bystander Effect In Lymphocytes That Insupporting
confidence: 80%
See 2 more Smart Citations
“…3) clearly shows that irradiated rho + yeast cells induced BE is much stronger than the rho 0 cells. These results confirm the view that strength of bystander effect depends on existence of mitochondrial DNA and normally functioning mitochondria [4].…”
Section: Manifestation Of the Bystander Effect In Lymphocytes That Insupporting
confidence: 80%
“…This phenomenon has been described in wide variety of vertebrate cell types, and to a lesser extent in other Metazoa cells and several unicellular organisms [2,3]. It was shown that BE is not cell-type dependent and can be induced in mixed cell cultures containing cells of different lines or cells derived from different species [4]. In addition, there is evidence for the existence of BE-like interactions in vivo in animals [5], in plants [6], as well as between cohabiting individuals of the same species [7,8].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This study, together with several other studies (Lyng et al, 2000(Lyng et al, , 2002Limoli et al, 2003;Maguire et al, 2005;Murphy et al, 2005;Nugent et al, 2007;Tartier et al, 2007;Chen et al, 2008), suggested that mitochondria represent the sensor of radiationinduced ionisation events. In this study, we showed that Cyt c-null cells can respond to radiation normally in ROS/NO generations as Cyt c-normal cells (Figures 2B and 3B).…”
Section: Discussionmentioning
confidence: 86%
“…The 4-amino-5-methylamino-2 0 ,7 0 -difluorofluorescein diacetate (DAF-FM diacetate) and 5-(and-6)-chloromethyl-2 0 ,7 0 -dichlorodihydrofluorescein diacetate, acetyl ester (CM-H 2 DCFDA) (Molecular Probes, Eugene, OR, USA) were used to quantify the level of NO and ROS, respectively, as described (Wan et al, 2005;Chen et al, 2008). In brief, cells at confluency were stained with 5 mM DAF-FM diacetate in Tyrode's solution or 2 mM CM-H 2 DCFDA in D-Hanks for 30 min in incubator, and then washed twice with the proper buffer respectively.…”
Section: Micronuclei Ros and No Testmentioning
confidence: 99%